FORMULATION AND EVALUATION OF LYCOPENE LOADED COLLOIDAL MICROPARTICLES GEL - BANSAL, MONISHA; WALIA, MANPREET KAUR; SINGH, GURFATEH; HARIKUMAR, S. L. (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of the present investigation was to design and evaluate a gel containing lycopene loaded colloidal microparticles. Methods: The lycopene loaded colloidal microparticles were successfully prepared by Cloud point technique to form colloids using Tween 40 and Tween 60 surfactant solution and then incorporated into microparticles by solvent evaporation method using polymer like HPMC and ethyl cellulose. These colloidal microparticles were evaluated for particle size (PS), drug loading (DL), entrapment efficiency (EE), Scanning Electron Microscopy (SEM). Further, these colloidal microparticles were incorporated into a topical formulation i.e., gel. This topical formulation was then evaluated for macroscopic examination, viscosity, drug content, spreadability, antioxidant activity, in vitro permeation and release kinetics. Results: Colloidal microparticles were successfully prepared and the particle size, drug loading and entrapment efficiency were found to be 249.45±14.2 μm, 49.8±0.96 % and 93.4±0.26 % respectively. FTIR study depicted no chemical interaction between pure drug lycopene and other excipients. The topical formulation showed sustained release and followed Korsmeyer-Peppas release kinetics model. Conclusion: The sustained release topical formulation of lycopene was successfully prepared using Tween 40 and Tween 60 surfactant solution and combination of HPMC and ethyl cellulose and evaluated for several parameters.